Application of Response Surface Method (RSM) to Optimize 3D Printer Process Parameter by using Polylactic Acid (PLA) Material - Koh Kai Li; Chee Kiong, Sia (Research Progress in Mechanical and Manufacturing Engineering, 2024)
In this modern era, the process of Fused Deposition Modelling (FDM) developed well in the manufacturing industry. However, there were still some different types of defects found in the 3D printing process. This study performed the optimization of 3D printer process parameters by using the optimization method, Response Surface Method and the Design of Experiment (DoE) was Central Composite Design (CCD). The material used in this study is polylactic acid (PLA). The aim of the study was to decrease the defects in the 3D printed products and obtain the optimal process parameter. The 3D printer used in this study was Anycubic Chiron and the filament applied was PolyLiteTM PLA. The model applied in this study was an All in One 3D Printer Test specimen which obtained from Thingiverse. The inputs included were printing temperature, printing speed, first layer height, and the ability of retraction. 16 sets of data had been prepared to find the most optimal process parameter set. Based on the result from Response Surface Method (RSM), the optimal process parameters are 40mm/s (printing speed), 190°C (printing temperature), 0.3mm (first layer height), and disable the retraction function. The experiment is assumed conducted successfully since the defects had been reduced from the optimized model.